Sam Chermayeff (et al.) - creatures - Chermayeff, Sam 1981-; Küng, Moritz 1961- (Apartamento Publishing S.L., 2020)
'Sam Chermayeff [et al.]: Creatures', edited by Moritz Küng, is a look back through nearly two decades of experimental projects undertaken by the Berlin-based architect Sam Chermayeff and his collaborators - for the most part pieces of furniture whose use, appearance, or application has been reimagined and readapted. But these "creatures" are not just conceptual; they're made to be lived with daily and all start with the idea that personal whim is probably the best guide for producing any design that's to be lived with day in, day out. Photos of these objects go hand in hand with an essay by writer and curator Dieter Roelstraete, who talks us through Chermayeff's work in the context of "thing theory", a school of thought that focuses on human-object interactions. Readers move back and forth between their own view of Chermayeff's creatures and Roelstraete's reflections on the nature of "things", as he also draws on cultural figures like Heidegger, Francis Ponge, Marina Tsvetaeva, and Karl Ove Knausgård, and our relationship to the indomitable presence of objects in our lives
Keywords: Chermayeff, Sam -- 1981-